2018
DOI: 10.3184/174751918x15314837408346
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure and Biological Evaluation of Novel 2-Phenylthiazole Derivatives as Butyrylcholinesterase Inhibitors

Abstract: To find novel butyrylcholinesterase inhibitors, three novel 2-phenylthiazole derivatives were synthesised. The synthesised compounds were characterised by NMR and single-crystal X-ray diffraction analysis. Hirshfeld surface analysis and two-dimensional fingerprint plots of the compounds were used as a theoretical approach to assess the driving force for crystal structure formation via the intermolecular interactions in the crystal lattices of the synthesised compounds. Among the three compounds, N-(1,5-dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…160,161 The role of BChE in normal conditions of healthy brain activity is overlooked, even though BChE level rises in tandem with AD progression in the latter phases of the illness. Remarkably, the level of AChE begins to decrease in these situations 162–164 (Fig. 10).…”
Section: Synthetic Sources Of Che Inhibitorsmentioning
confidence: 86%
“…160,161 The role of BChE in normal conditions of healthy brain activity is overlooked, even though BChE level rises in tandem with AD progression in the latter phases of the illness. Remarkably, the level of AChE begins to decrease in these situations 162–164 (Fig. 10).…”
Section: Synthetic Sources Of Che Inhibitorsmentioning
confidence: 86%
“…The SAR analysis indicated that p-tolylthiazolyl and dimethoxybenzylidene were observed in 124a, while in the case of 124b, methoxyphenylthiazolyl and methoxybenzylidene groups were essential requirements for the activity [159]. The SAR analysis indicated that the existence of (5-thiomorpholinopentyl) oxy groups was the prime requirement to exhibit anti-Alzheimer's activity [144]. Novel thiazolyl hydrazine compounds were developed and produced based on the chemical structure of the donepezil molecule.…”
Section: Thiazoles As Anti-alzheimer Agentsmentioning
confidence: 99%
“…Thereafter, in multiple steps, the final compounds were produced. With IC50 values of 5.19 μM and 5.83 μM, compound 109 displayed the best acetyl cholinesterase and butyryl cholinesterase inhibition abilities.The SAR analysis indicated that the existence of (5-thiomorpholinopentyl) oxy groups was the prime requirement to exhibit anti-Alzheimer's activity[144]. Novel thiazolyl hydrazine compounds were developed and produced based on the chemical structure of the donepezil molecule.…”
mentioning
confidence: 99%